The Educational Use of the Smartphone by University Students of Social Education and Social Work - López-Noguero, Fernando; Gallardo-López, José Alberto (Revista Fuentes, 2022)
A smartphone is a mobile device increasingly present in the academic activities that take place in universities, becoming a technological tool with great educational potential. The goal of this research is to analyze how students use their smartphones in university contexts, and how they evaluate the use of these mobile devices as educational tools. The research methodology used responds to an ex post facto, quantitative, transversal, correlational and descriptive design, with a sample of 252 university students of Social Education and Social Work of the Pablo de Olavide University (Seville, Spain). As a method for collecting data the questionnaire "Smartphone and university. Student’s vision. SUOS" has been used. The research work provides outstanding conclusions for the field of study addressed, among the main results obtained, it is emphasized that the university students show a clear positive evaluation of the use of the smartphone as an educational tool in Higher Education, with the youngest students being those who use the smartphone the most at the university level. Also, numerous advantages stand out, such as the rapid search for information, access to content without spatial or temporal limitations, as well as its usefulness for academic management and organization and communication with other students, promoting the development of their learning. On the other hand, there are some negative aspects of the use of Smartphones in university contexts, such as dependency and stress that can lead to the misuse of this technology, or the negative impact that it can have on written communication.